An Analysis of the Service Marketing and Service Quality of Broadcasting Companies in the United Kingdom - Stath, Ulrike (2007)
The field of television broadcasting is interesting and a complex one from a business studies point of view since it is a fast moving industry. The main challenge faced by companies is the need to take into account innovation and customer orientation in order to remain competitive. Due to increased competition, services and their quality have become considerably important for businesses. The aim of this dissertation is to give an overview of the services of four broadcasting companies that either have shaped the broadcasting landscape in the United Kingdom or have the potential to have a sincere impact in the future. The BBC, British Sky Broadcasting (BSkyB), Virgin Media, and Joost were selected and examined using models of service marketing. In addition, a sketch of future developments of broadcasting technologies and customer demand and their impact on the broadcasting services is presented. The analysis of all four broadcasters revealed several opportunity areas mainly in the field of e-services. The paper culminates in the provision of suggestions for the companies to improve their services.